Single-grain OSL chronologies for the Still Bay and Howieson's Poort industries and the transition between them: Further analyses and statistical modelling. Issue 107 (June 2017) - Jacobs, Zenobia; Roberts, Richard G.
Abstract: The chronology of the Still Bay (SB) and Howieson's Poort (HP) lithic industries remains an issue of keen interest because of the central role of these two phases of technological and behavioural innovation within the Middle Stone Age of southern Africa. Several dating studies have been conducted on SB and HP sites, including a pair published by the present authors and our colleagues in 2008 and 2013. These reported the results of systematically applying single-grain optically stimulated luminescence (OSL) dating procedures to 10 sites in South Africa, Lesotho and Namibia to constrain the timing of the start and end of the SB and HP and reveal the existence of a gap of several millennia between them. Alternative ages for these two industries have since been proposed by others for one of these South African sites (Diepkloof Rockshelter) and some concerns have been raised about the procedures used in our earlier studies to estimate the beta dose rates for a small number of samples. Here, we provide an update on our chronology for the SB and HP and address the issues raised about the methods that we used previously to estimate the beta dose rates and their associated uncertainties. To test the sensitivity of our new SB and HP ages to different underlying assumptions, we have run the same statistical model as that used in our 2008 and 2013 studies under three different scenarios. We show that the ages for the different samples are insensitive to how we analytically process or statistically model our data, and that our earlier conclusions about timing of the start and end of the SB and the HP and the probability of a gap between them remain true for two of the three scenarios. We conclude by bringing our study into the context of additional chronometric, stratigraphic and lithic technology studies that have been conducted in the intervening decade.